MANAGING COMMUNITY-BASED ECOTOURISM IN BANYUWEDANG BAY BALI AND ITS IMPLICATIONS FOR VISITOR SATISFACTION - I Ketut Surya Diarta; Pitana I Gde (Department of Forest Resources Conservation and Ecotourism - IPB University, 2022)
Ecotourism in Banyuwedang Bay Bali is run with community-based principles (CBE). The local community is the determining entity to the extent that the implementation of CBE affects the attributes and services provided to visitors, thereby determining visitor satisfaction. The aims of this study are: (a) to analyze the level of CBE implementation, and (b) to analyze the effect of ecotourism attributes and services on visitor satisfaction. The results showed that the level of CBE implementation in Banyuwedang Bay was classified as fully implemented and very good. Full business ownership by the local community who simultaneously manages all activities in ecotourism independently. There is a significant influence of the attributes and quality of ecotourism services on visitor satisfaction. The findings of this study should dispel skepticism about the inability of local communities to manage ecotourism. It is recommended that the government provides trust and authority as well as adequate assistance to local communities in developing similar ecotourism independently and in mutual cooperation. The assistance needed is related to ecotourism management training and service quality management to visitors, considering that both have a significant effect in shaping visitor satisfaction. This research has a limited scope of study area, so to obtain a more general conclusion, a wider scope of research is needed on several community-based ecotourism destinations throughout the Bali region. Key words: ecotourism, attribute, service, satisfaction, Bali